The return of the historic influenza A H1N1 virus and its impact on the population of the United Kingdom. - Chakraverty, P. (Cambridge University Press, 1982)
The epidemiology in the United Kingdom of the influenza A H1N1 subtype which returned in 1977 after an absence of 20 years in described for the four winter seasons from 1977/8 to 1980/1. The age distribution of virus isolates and the evidence for antigenic variation is presented. The impact in the susceptible age groups year by year is shown by the change in the population with specific antibody. There was the expected increase of antibody in those under the age of 21 but also evidence for a significant amount of infection or re-infection in the older adult population.